2001
DOI: 10.1007/s11882-001-0048-9
|View full text |Cite
|
Sign up to set email alerts
|

The genetics of otitis media

Abstract: There is significant evidence from epidemiologic, anatomic, physiologic, and immunologic studies that susceptibility to recurrent episodes of acute otitis media (OM) and persistent OM with effusion is largely genetically determined. The genetics of OM are most likely complex, i.e., many genes are probably contributing to the overall phenotype. The knowledge of a hereditary component has important implications because closer surveillance of children at risk for OM could result in earlier detection and treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…In our model, children with a family history of OM had an increased risk of AOM (OR 1•59, P = 0•02). A similar result was observed in families in Greenland [29] and researchers have suggested a genetic link for OM risk [30]. In our study population we found that breastfeeding for 56 months did not diminish the risk for AOM more than breastfeeding for a shorter time.…”
Section: Discussionsupporting
confidence: 91%
“…In our model, children with a family history of OM had an increased risk of AOM (OR 1•59, P = 0•02). A similar result was observed in families in Greenland [29] and researchers have suggested a genetic link for OM risk [30]. In our study population we found that breastfeeding for 56 months did not diminish the risk for AOM more than breastfeeding for a shorter time.…”
Section: Discussionsupporting
confidence: 91%
“…Although AOM can occur at any age, it is most common in young children, particularly at the age of 6–24 months (Pukander et al 1982; Lundgren and Ingvarsson 1983; Teele et al 1989). A genetic component engrossed in the predisposition to middle ear infections (Casselbrant and Mandel 2001). …”
Section: Discussionmentioning
confidence: 99%
“…The most common ethiologies of tubal dysfunction are functional problems [1] and its intrinsic system of opening and closing [5][6][7][8], immunological [9] and genetic disorders [10], gastroesophageal reflux [11] and rhinosinusitis [5,12]. Enlarged adenoid is another associated factor, once it obstructs the pharyngeal ostia of the auditory tube [12,13].…”
Section: Introductionmentioning
confidence: 99%